Properties and characterization of bio-adhesive based wood composite. - Hashim, Rokiah
Wood based composites are widely used renewable panel products in manufacture of many applications including furniture and cabinet production as well as structural purposes. Formaldehyde based adhesive such as urea-formaldehyde and phenol-formaldehyde are still most commonly binders used in wood composite industry today.